Vitamin D Level in Adult Allergic Conjunctivitis Patients: A Systematic Review - Putri, Maria Evane Navy Cahaya; Irawan, Empi (Oftalmologi : Jurnal Kesehatan Mata Indonesia, 2025)
Introduction: Allergic conjunctivitis is an immune-mediated ocular inflammation, and this study reviews evidence on the association between vitamin D levels and disease severity in adults. Methods: A systematic literature search was conducted using PubMed, Scopus, Web of Science, and Google Scholar for articles published between 2015 and 2025. Observational studies and clinical trials evaluating vitamin D status in adults with AC were included. Of 50 articles screened, four studies comprising 375 adult participants fulfilled the eligibility criteria. Extracted data included study design, vitamin D measurement methods, clinical outcomes, and statistical results. Risk of bias was assessed using ROBINS-I and Cochrane RoB 2.0, and the review followed PRISMA guidelines. Results: The included studies consisted of two observational studies and two clinical trials. Lower vitamin D levels were significantly associated with more severe AC symptoms in two observational studies. One clinical trial demonstrated mild symptomatic improvement following vitamin D supplementation, while another showed no significant effect. Variations in diagnostic criteria, laboratory methods, and confounding factors limited comparability. Conclusion: Lower vitamin D levels may enhance AC severity in adults. Further robust clinical trials are warranted to confirm these findings and to explore vitamin D supplementation's therapeutic role.